“Em busca da mancha”: a atuação policial nos bairros do Jurunas e da Batista Campos - FERNANDES, Antonio José Martins (Universidade Federal do Pará, 2023)
The present work seeks to reflect on how the performance of the Military Police differs within the neighborhoods of Jurunas and Batista Campos, in the city of Belém-Pará. In order to carry out the research, inductive and comparative methods were adopted, based on bibliographic and documentary survey techniques, as well as semi-structured interviews with military police officers who work directly in the studied neighborhoods. The research aimed, in the first part of its development, to analyze the historical formation of the territories of the neighborhoods and the relationship with the social markers of race and class. Based on this, in the second section, it was also intended to understand the police action in these areas and how it differs according to the territory, as well as what are the most evident aspects of this differentiation. In the last part of the development, the analysis turned to the relationship of these main aspects of differentiation with the structures of class, race and, mainly, territory and how this changes the performance of the PM. This led to the conclusion that the PM, structured on the basis of inequalities of race, class and territory, works as an armed wing in the streets to guarantee the interests of the elite while promoting the control of the vulnerable population.